Implementation of the Game-Based Learning Method in the Akidah Akhlak Subject to Improve Students’ Learning Outcomes at MTs Al-Ukhuwwah Lok Bangkai - Helda Daniati; Ria Susanti (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
This study aims to determine the use of game based learning methods in improving student learning outcomes in the subject of Akidah Akhlak at MTs Al-Ukhuwwah Lok Bangkai. The subjects in this study were 24 class VIIC students at MTs Al-Ukhuwwah Lok Bangkai. While the object of this study is the implementation of the game based learning method to improve the learning outcomes of class VIIC students at MTs Al-Ukhuwwah Lok Bangkai. This study was carried out in two cycles, each cycle consisting of four stages, namely planning, implementation, observation, and reflection. The techniques used in data collection are tests, observation sheets and documentation. The results of the study indicate that implementing the game based learning method can improve student learning outcomes in the subject of Akidah Akhlak at MTs Al-Ukhuwwah Lok Bangkai. Improvement in student learning outcomes can be seen from each cycle. In cycle I, the first meeting, the average student score was 77.91 with a percentage of 66.67%, then the average student score increased to 80.62 with a percentage of 87.50% in cycle I, the second meeting, and in cycle II, the first meeting, the average student score was 90.62 with a percentage of 87.50%, then the average student score increased to 94.79 with a percentage of 91.67% in cycle II, the second meeting. As a result, students were able to accept the material presented and there was a change, namely an increase in learning outcomes, especially in the subject of Aqidah Akhlak